Quantum Dots Recent Advances, New Perspectives and Contemporary Applications - Thirumalai, Jagannathan (IntechOpen, 2023)
This book provides a detailed overview of recent advances in the captivating world of quantum dots and outlines some possible imminent new directions for this important field. A variety of advanced techniques is rapidly developing in the application of quantum dots to solar photovoltaics, LEDs, quantum computing (qubits) and different biological spheres. The book presents, discusses and compares devices based on state-of-the-art structures, incipient material and new physical effects. Improved efficiency and reliability in these fields are already pointing the way to next-generation devices, especially in the nano regime. This book is addressed to students and scientists working in the field of quantum dots and progressive technologies.